Farmers perceptions of practices and constraints in cassava (Manihot esculenta Crantz) chips production in rural Cameroon - Essono , G.G.; Ayodele, M.; Foko, J.; Akoa, A.; Gockowski, J.; Ambang, Z.; Bell, J.M.; Bekolo, N. (2008)
A survey aimed at collecting information on practices and constraints in the production of cassava (Manihot esculenta Crantz) chips, a transformed cassava product obtained through fermentation and drying of its fresh roots was carried out in 45 villages located in three geographical regions (Yaoundé, Mbalmayo, and Ebolowa) of the humid forest zone of Cameroon. A structured questionnaire to interview farmers was employed. Out of 225 farmers sampled, 212 (94%) relying on chips as food and source of income were women. Overall, 51% of all farmers marketed chips locally. Three distinct forms of chips such as broken pulp (62%), balls (25%), and pellets (13%) were cited as being locally produced by farmers. These were obtained either through air fermentation (cassava pellets), or submerged fermentation (broken pulps and balls), using starters or fermenting agents (31% of responses) or without using them (69%). Chips were mainly home-stored in jute and orplastic bags (43% of responses), open or closed containers (36%), or on devices hanging over the fireplace (21% of responses) for as long as 180 days. Dark spots or discolouration occurring as a result of chips damage were reported by the majority of respondents (82%) as frequent on cassava chips. These were related to insufficient drying (42%), the use of infected cassava roots by plant pathogenic microbes from the fields (12%), or too long drying of chips under sun light (11% of responses). To avoid dark spots andor discolouration, 112 farmers out of a total of 185 who were aware about chips damage, practiced sundrying, and 21% of this total dried their chips over the fireplace to control chips damage. Pests and diseases problems (47% of responses), mainly related to the incidence of Stictococcus vayssierei Richard (Homoptera: Stictococcidae) and lack of market (26%) were cited by farmers as the most important constraints in cassava chips production. From the results obtained, this study outlined that the potential utilization of cassava and its derived products for industrial purposes is not yet exploited in the locations investigated. Additionally, the study also raised concerns about the safety and hygiene associated with traditionally processed and stored cassava chips in the investigated areas.